(3GdCHMGK GdeSOOI aj afhf eJYOOIs - (3UGdM Hf egOi Hf Ydj GdebHdi Gdjefis
(3ChdgG (B:s
(3Ef bdJ gd GdeQGO GdeJUahf HGdJbhi MbjbI Ch eLGRkG Ci ef Yde Gddg efge Pdc eWdbkG s
(3BNQgG (B:s
(3heG COQGc eG jhe GdaUd , GfJgJ GdCeKGd addg GdMeO s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3YdjgG Pjd GdCHMGK GdeSOOI hMd eSGFdgG GdeYbOI deMeO Hf GSeGYjd Hf UdGM GdCejQ GdMSfi GdUfYGfi UGMH SHd GdSdGe (B1182 (3g`s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
Keywords: (3eJaQbGJs